Analysis of throw-ins strategy on performance metrics in five men`s European football leagues - Stone, Joseph. A.; Kubayi, A.; Smith, A.; North, J. S. (International Journal of Performance Analysis in Sport, 2025)
Limited research has investigated the impact of throw-in strategy on match performance. Hence, this study examined throw-in strategy used by teams across five European competitions and how that strategy affected first contact success, possession retention, and attacking outcomes. Throw-ins from 1,826 matches across five European Leagues (Premier League; Bundesliga; Serie A; La Liga; Ligue) during the 2022/2023 season were analysed. StatsBomb data resulted in 71,220 phases of play originating from a throw-in. Variables such as competition, throw-in distance and direction were assessed on their impact on first contact success, possession metrics and shot creation. On average, 39 throw-ins were taken per match. 42287 throws originated from the middle zones of the pitch, with throwing the ball backwards (99.5%) or laterally (96.9%) increasing first contact success compared to throwing the ball forwards (71.3%) (p < 0.05). Quicker throw-in restarts resulted in an increased first contact success rate (0-5 seconds, 94.4%, compared to 78.31% >15 seconds). Retaining possession from the throw-ins was highest when going backwards (92.13%) compared to laterally (71.20%) and forwards (49.75%). Results showed an increased chance of shot creation for throw-ins directed backwards or laterally compared to those directed forwards. Findings are discussed in relation to applied performance and coaching implications.